Computer Programming Language: Depth Classification Version of CC - Ravichandra Rao, I. K.; Rawat, Kanti (Journal of Information and Knowledge, 1972)
A depth classification version of Colon Classification for compound subjects going with the Host Subject " 9S,8 Computer Programming Language" is given. The methodology of design is based on that for freely faceted classification. Computer Programing Language is deemed to be a Personality Isolate going with the Main Subject " 9s Computer Science". The principles used in arranging the speciators derived on the basis of different quasi-isolates are mentioned. An Index to the schedule, a list of twenty-four examples classified according to the depth version, and an alphabetical index to the subjects in the classified list of examples, are given.